Bannayan‐Riley‐Ruvalcaba syndrome with gingival hyperpigmentation and facial papules. Issue 5 (14th July 2021) - Niklinska, Eva B.; Lyons, Eden Marie; Hicks, Alexander; Zwerner, Jeffrey P.; Albers, Sharon E.
Abstract: One of the distinctive cutaneous manifestations of Bannayan‐Riley‐Ruvalcaba syndrome (BRRS), a PTEN hamartoma tumor syndrome, is penile pigmented macules. We present a 13‐year‐old boy with gingival hyperpigmentation along with facial and ear angiofibromas in the context of a BRRS‐concordant phenotype and PTEN hamartoma tumor syndrome genotype. To our knowledge, these two findings have not been previously reported with BRRS and may expand the known phenotype of this disorder.